"Tobacco-free" Nicotine Pouches: Risk Perceptions, Awareness, Susceptibility, and Use Among Young Adults in the United States. Issue 1 (24th August 2022) - Morean, Meghan E; Bold, Krysten W; Davis, Danielle R; Kong, Grace; Krishnan-Sarin, Suchitra; Camenga, Deepa R
Abstract: Background: Nicotine pouches containing synthetic nicotine or tobacco-derived nicotine (TDN) are available in the United States. Synthetic nicotine pouches are often marketed as "tobacco-free nicotine" (TFN), which may alter risk perceptions and product appeal. This study examined young adults' perceptions of TFN versus TDN pouches and the associations between product perceptions and TFN pouch awareness, susceptibility, and use, respectively. Aims and Methods: In total 630 young adults (18–25 years) completed an online Qualtrics panels survey in 2021. Participants were informed that TFN pouches contain synthetic nicotine as opposed to TDN. Participants reported on comparative risk perceptions for TFN versus TDN pouches and on TFN pouch awareness, susceptibility, and use. Unadjusted between-group comparisons and adjusted binary logistic regressions were run to examine relationships between product perceptions and TFN pouch awareness, susceptibility, and use. Results: Participants were aware of (37.3%), susceptible to (29.2%), or had used TFN pouches (3.8%). In unadjusted comparisons, TFN pouch awareness, susceptibility, and use were associated with disproportionately perceiving TFN pouches as less harmful or otherwise better than TDN pouches. In adjusted models, relationships between favorable perceptions and both TFN pouch awareness and susceptibility remained significant. Conclusions: The descriptor "tobacco-free" may impact risk perceptions and the appeal of nicotine pouches among young adults. While no direct relationship was observed between TFN perceptions and TFN pouch use in the adjusted model, perceptions remained related to product awareness and susceptibility, which may be linked to future use. Continued surveillance is needed to fully determine how the term "tobacco-free" on product packaging and advertising impacts longitudinal public health outcomes. Implications: Nicotine pouches originally contained TDN. Today, numerous brands of synthetic nicotine pouches, which are often marketed as "tobacco-free, " are available on the market. We informed participants that "tobacco-free nicotine" pouches contain synthetic nicotine and examined comparative risk perceptions (i.e. tobacco-free vs. TDN pouches) and TFN pouch awareness, susceptibility, and use. Perceiving tobacco-free nicotine pouches as less harmful than tobacco-derived pouches was associated with product awareness, susceptibility, and use in unadjusted models and with awareness and susceptibility in adjusted models. Restricting the term "tobacco-free" may become necessary if the term inaccurately reduces product risk perceptions or increases product appeal.